The Issue of Definition in the School Dictionary: Analytical and Critical Study in an Algerian School Dictionary "Al-Wajeez" - بلقاسم نوارة; ختيم عزوز (Milev Journal of Research and Studies, 2023)
The main topic of this article is related to the issue of definitions in school dictionaries, because definition is the core of any lexicon, so lexicographers publish different types of definitions to explain their general terms or scientific terms. This research aims to know a number of issues related to the types of definitions used in the dictionary of the Algerian school, the case of "Al-Wajeez" Dictionary, and to analyse how it defines terms and brings them closer to the learner's mind